The Effect of Establishing Escherichia coli on Balb/C Rats as A Model of Preterm Labor - Suheni Ninik Hariyati; Dewi Santosaningsih; Arief Satria Hardika; Fikhy Rizky Hapsari; Nirwan Nugraha L.; Wildan Aulia Firdaus (Ikatan Dokter Indonesia Wilayah Jawa Timur, 2023)
Introduction: The prevalence of preterm labor in Indonesia is estimated at 7-14%, which is around 459,200-900,000 babies per year. The mechanism of infection is the biggest cause of preterm labor. The bacteria that often causes infection is Escherichia coli. This study aims to see the effect of giving Escherichia coli to produce premature models of mice. Material and Methods: This study used a true experimental method with a post-test only control group design approach. The independent variables were preterm labor & cervical tissue culture, amniotic membranes, and placenta. The dependent variable of the study was the administration of Escherichia coli 109 CFU to the cervix. This research will be tested with a comparative test. Results: The treatment group were given Escherichia coli experienced parturition with the fastest time of 38 hours 22 minutes and the longest time of 42 hours 12 minutes. Escherichia coli colonies on Eosin Methylene Blue (EMB) culture media with a glowing green image was obtained. Cervical culture, amniotic membranes and placenta from the treatment group of Balb/C mice showed the growth of Escherichia coli colonies. Neutrophil infiltration and edema in the cervical stroma was found to be more severe in Balb/C mice that received treatment with Escherichia coli 109 CFU/ml. Conclusion: Escherichia coli shortens the time of delivery and increases the bacterial load in pregnant Balb/C mice.